2013
DOI: 10.1002/adsc.201300266
|View full text |Cite
|
Sign up to set email alerts
|

Ethynylbenziodoxolones (EBX) as Reagents for the Ethynylation of Stabilized Enolates

Abstract: Abstract. Herein, we report a detailed study on the electrophilic alkynylation of cyclic keto-esters and amides with ethynylbenziodoxolone (EBX) reagents. The structure and stability of this class of reagents is first described more in details. DSC experiments showed a strong exothermic decomposition with EBX reagents, leading to guidelines for the safe use of these compounds. The extension of the method to aromatic alkynes and a broad range of benziodoxol(on)e reagents is then reported. Based on our prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 40 publications
1
34
0
5
Order By: Relevance
“…On a 0.40 mmol scale, azide 3a could be isolated in 94% yield (entry 1). The azidation (10) In their first communication, 9a Zhdankin and co-workers indicated that these reagents may also react with nucleophiles derived from carbonyls, but the result of such reactions was never reported. proceeded in good yields independent of the electronic properties of the substituent on the benzene ring of indanone (entries 2-4).…”
Section: Scheme 2 Azidation Of Keto Ester 1amentioning
confidence: 99%
See 1 more Smart Citation
“…On a 0.40 mmol scale, azide 3a could be isolated in 94% yield (entry 1). The azidation (10) In their first communication, 9a Zhdankin and co-workers indicated that these reagents may also react with nucleophiles derived from carbonyls, but the result of such reactions was never reported. proceeded in good yields independent of the electronic properties of the substituent on the benzene ring of indanone (entries 2-4).…”
Section: Scheme 2 Azidation Of Keto Ester 1amentioning
confidence: 99%
“…9 The reactivity of these reagents was studied for the radical-based azidation of aliphatic C-H bonds. 9,10 During completion of our work, Gade and co-workers reported the first catalytic asymmetric method for the azidation of -keto esters and oxindoles using a chiral iron catalyst together with an azidobenziodoxole reagent. 11 This major breakthrough motivate us to report our own preliminary results in the area, including the very efficient azidation of cyclic -keto esters with azidobenziodoxole 2 in the absence of any catalyst and the zinc-catalyzed azidation of less reactive linear keto esters and silyl enol ethers using the same reagent (Scheme 1).…”
mentioning
confidence: 99%
“…Higher selectivities around the 60 % ee value were again observed starting from the α‐tetralone 5 g or the bulky ester‐bearing 1‐indanone 5 i (Table ). These results underline the substrate‐dependent efficacy of this chiral iodane‐mediated asymmetric alkynylation reaction, as in the case of TMS‐EBX use in the presence of a chiral catalyst . However, it is interesting to note that enantioinduction from our bis(alkynyl‐λ 3 ‐iodane) atropisomers (up to 68 % ee ) does not necessitate the presence of a bulky ester alkyl group onto the substrates (i.e., Me vs. t Bu or CMe 2 Ph, see Scheme ) …”
Section: Methodsmentioning
confidence: 61%
“…11 A ligação de um acetileno a iodo(III) resulta em um reagente de iodo hipervalente com um carbono com polaridade invertida (umpolung). 9,18 Estes reagentes alquinilantes eletrofílicos têm sido usados para a funcionalização de diversas classes de compostos, em especial compostos carbonílicos, visto que muitos deles apresentam elevada estabilidade e baixa toxicidade (Esquema 2). 9,12,17 Especialmente os reagentes derivados da EtinilBenziodoXolona (EBX) têm sido os mais utilizados nos últimos anos pois eles permiten reações de alquinilação eletrofílicas não comuns, mas altamente úteis.…”
Section: Introductionunclassified
“…15,20 Apesar disso, foi necessário utilizar catalizadores metálicos (Au(III) e Pd(II)) para aumentar a eletrofilidade do grupo alquino a ser inserido. 18 Esquema 3. Alquinilação eletrofílica de aromáticos cíclicos desenvolvida por Waser e colaboradores.…”
Section: Introductionunclassified